School Branding Design Training : Logos, Banners , and Digital Presentation Templates For Student SMK Negeri 3 Kayuagung - Dwi Fitri Brianna; Paisal; Mariana Purba; Bakhtiar .K (CogniSpectra Publishing, 2025)
Background: Graphic design is skills important in the digital era, especially in context build and strengthen visual identity of a institutions , including institution education . The school's visual identity — such as logos, banners , and presentation templates — plays a role in emphasize character , vision , and image institutions in the eyes public . Therefore that , understanding and skills in field design graphic become need strategic for students , especially in schools Intermediate Vocational (SMK) which is oriented towards mastery skill practical . Activities training This implemented as form contribution real through community service programs to society , with objective main equip student with skills design relevant and impactful graphics​ direct to identity school . Contribution: Method applied training​ is approach participatory and practical directly (learning by doing). During activities , students in a way active involved start from understanding base about draft design , exploration school visual identity , to the creation process work design use device soft graphic approach​ This selected so that students No only understand theory , but also has experience concrete in apply principles design in a way contextual Method: Method applied training​ is approach participatory and practical directly (learning by doing). During activities , students in a way active involved start from understanding base about draft design , exploration school visual identity , to the creation process work design use device soft graphic approach​ This selected so that students No only understand theory , but also has experience concrete in apply principles design in a way contextual Results: Training results show that student capable produce work creative , functional , and representative digital design to identity school . Products The resulting designs — such as logos, banners , and presentation templates — can be direct used in various activity school . Besides achievements technical , activities this also proves existence improvement motivation , creativity , and caring student to development visual image of the school they.